New Standards in the Treatment of Advanced Metastatic Melanoma: Immunotherapy and BRAF-Targeted Therapies as Emerging Paradigms - Kreidieh, Firas; Wong, Michael K. (Current Pharmaceutical Design, 2026)
Although cutaneous melanoma accounts for only about 2% of skin cancers, its rapid progression makes it an aggressive skin cancer with a high mortality rate. As of 2018, the SEER database estimated that the 5-year overall survival (OS) rate is 29.8% in patients with stage IV disease at diagnosis in the United States. Non-cutaneous melanoma, including mucosal and uveal subtypes, carries a generally worse prognosis. Once considered refractory to conventional treatments, such as chemotherapy and radiation therapy, the advent of immunotherapy, including immune checkpoint inhibitors (ICIs), vaccines, and tumor-infiltrating lymphocytes (TIL), and of targeted therapy over the past decade has resulted in dramatic improvements in melanoma. Importantly, ICIs have resulted in long-term remission for patients with melanoma, thus introducing the possibility of a cure for some patients with metastatic disease. These include antibodies against programmed cell death-1 (PD-1)/programmed cell death ligand-1 (PD-L1), cytotoxic T-lymphocyte antigen-4 (CTLA-4), and lymphocyte activation gene-3 (LAG-3). In this review, we will provide an overview of metastatic melanoma while focusing on its current pharmacologic armamentarium, toxicities of treatment, including ICIs and targeted therapy, and its therapeutic clinical strategies. The therapeutic advances presented in this review serve as the foundation for an ever-expanding repertoire of innovative approaches. These include mRNA vaccines, oncolytic viruses, bispecific engagers, oral immunomodulators, and novel cytokines. Adoptive cellular strategies are evolving to TILS transduced with conditional gene expression cassettes, as well as non-T cell approaches involving dendritic cells and natural killer (NK) cells. Targeted therapy strategies have broadened to include upstream components of RAS, other MAP kinase pathways, and HDAC inhibitors, among others. All these new paradigms translate into increasingly complex decision-making for the treatment team, a burden that is more than offset by the tremendous benefit for melanoma patients. This is truly the beginning of a new era.
Keywords: tumor-infiltrating lymphocytes